La Durée. - Runólfsson, Halldór Björn; Thórsdóttir, Harpa; National Gallery of Iceland, Reykjavik (Reykjavik : National Gallery of Iceland, 2008)
Antille, Emmanuelle ; Fridriksdóttir, Gabriela ; Ingimarsdóttir, Gudný Rósa
National Gallery of Iceland, Reykjavik, 23.2 - 1.5.2008
kunstcatalogus